Effects of alternating injection-interruption periods on the fine particle transport and retention in granular media. Issue 1 (2nd January 2023) - Zaidi, Mohammed; Ahfir, Nasre-Dine; Alem, Abdellah; Taibi, Said; El Mansouri, Bouabid; Pantet, Anne; Zhang, Yongxiang; Wang, Huaqing
Abstract: This study investigates the impact of interruption of injections on the transfer and retention of suspended particles (SP) in granular media. Columns packed with sand were operated in the laboratory, and a series of experiments of SP injections were conducted: the first by injecting SP without interrupting injection, the second and third experiments with 3 pauses of injection of 24 h and 48 h, respectively. Results showed that interrupted injections induced a significant release of particles showing peaks of concentration in the effluent immediately after the pause periods. These peaks increase with pause durations. Interruption of injections allowed the transport of coarser particles deeper into the columns. For all experiments carried out, the hydraulic conductivity, measured during injection, decreased with the number of pore volumes injected. This decrease is almost linear for continuous injection experiments. Whereas, the hydraulic conductivity decreased brutally when reinjecting SP, after pauses, highlighting the desaturation of the porous medium during pause periods. The results obtained show that all the phenomena (hydraulic conductivity drop, SP transport, and deeper transfer of coarser particles) occurred during the dynamic phase of the experiments for the first 75% of pore volumes injected. Beyond that, the porous medium is completely clogged.